Transactional pathways of transgender identity development in transgender and gender-nonconforming youth and caregiver perspectives from the Trans Youth Family Study. Issue 3 (3rd July 2017) - Katz-Wise, Sabra L.; Budge, Stephanie L.; Fugate, Ellen; Flanagan, Kaleigh; Touloumtzis, Currie; Rood, Brian; Perez-Brumer, Amaya; Leibowitz, Scott
ABSTRACT: Background : A growing body of research has examined transgender identity development, but no studies have investigated developmental pathways as a transactional process between youth and caregivers, incorporating perspectives from multiple family members. The aim of this study was to conceptualize pathways of transgender identity development using narratives from both transgender and gender-nonconforming (TGN) youth and their cisgender (nontransgender) caregivers. Methods : The sample included 16 families, with 16 TGN youth, ages 7 to 18 years, and 29 cisgender caregivers ( N = 45 family members). TGN youth represented multiple gender identities, including trans boy ( n = 9), trans girl ( n = 5), gender-fluid boy ( n = 1), and girlish boy ( n = 1). Caregivers included mothers ( n = 17), fathers ( n = 11), and one grandmother. Participants were recruited from LGBTQ community organizations and support networks for families with transgender youth in the Midwest, Northeast, and South regions of the United States. Each family member completed a one-time, in-person semistructured qualitative interview that included questions about transgender identity development. Results : Analyses revealed seven overarching themes of transgender identity development, which were organized into a conceptual model: Trans identity development, sociocultural influences/societal discourse, biological influences, family adjustment/impact, stigma/cisnormativity, support/resources, and gender affirmation/actualization . Conclusions : Findings underscore the importance of assessing developmental processes among TGN youth as transactional, impacting both youth and their caregivers.